Wir haben folgendes: $$\int \frac{2(x^2-1)}{(1+x^2)^2}dx=2\int \frac{x^2-1}{(1+x^2)^2}dx \\ =2\int \frac{x^2-1+1-1}{(1+x^2)^2}dx \\ =2\int \frac{(x^2+1)-2}{(1+x^2)^2}dx \\ =2\left(\int \frac{x^2+1}{(1+x^2)^2}dx-\int \frac{2}{(1+x^2)^2}dx\right) \ =2\left(\int \frac{1}{1+x^2}dx-\int \frac{2}{(1+x^2)^2}dx\right) \\ =2\int \frac{1}{1+x^2}dx-4\int \frac{1}{(1+x^2)^2}dx$$
Es gilt dass $$\frac{1}{1+x^2}dx=\arctan (x)+c_1$$
Für das zweite Integral können wir die Reduktionsformel anwenden: $$\int \frac{1}{(ax^2+b)^n}dx=\frac{2n-3}{2b(n-1)}\int \frac{1}{(ax^2+b)^{n-1}}dx+\frac{x}{2b(n-1)(ax^2+b)^{n-1}}$$ mit a=1, b=1 und n=2.